INFLUÊNCIA DO MANEJO DA IRRIGAÇÃO E DA ADUBAÇÃO NITROGENADA NA PRODUÇÃO E QUALIDADE DE SEMENTE DE FEIJÃO - CULTIVAR IAC 2051 - Domingos Medeiros , Rodinei; da Silva Lopes , Adriano; da Silva Franco , Jhonatan; Gomes Miranda , Roger; Oliveira Pimenta Couto , Caio; Vitor de Oliveira Klip , Dioph (ANAIS DO ENIC, 2026)
-